Understanding the Concept of Elder Abuse from Islamic Perspective - Asiah, Bidin; Zulkifli, Mohd; Noor ‘Ashikin, Hamid; Kamaliah, Salleh (2017)
Elder abuse is not a new phenomenon. Even though elder abuse has been recognised as a social problem, a violation of human rights and a crime, on reality it is still a hidden issue. Despite the increase in the number of researches, the discussion of elder abuse from an Islamic perspective is still lacking. Most researches are still guided by western principles and theories. Very little attempt has been taken to analyse the issue from an Islamic perspective. This article aims to discuss elder abuse from an Islamic perspective. The focus of the discussions are on the status and rights of the elderly and parents in Islam with special reference to rights to be respected, rights for kind treatment, rights of care and rights for maintenance. In discussing the issue, provisions from al-Qur’an and the Sunnah were analysed in order to identify the concept and Islamic rulings on elder abuse.